Myeloid sarcoma arising at the uterine cervix in a patient with intestinal Behçet's disease and concurrent myelodysplastic syndrome: A case report. Issue 43 (28th October 2022) - Choi, Hwa Yeon; Pak, Min Gyoung; Park, Jung-Woo
Abstract : Introduction: Myeloid sarcoma (MS) is an extramedullary tumor that consists of myeloblasts and rarely involves the female reproductive organs. Intestinal Behçet's disease (BD) is a chronic, inflammatory illness that is often associated with myelodysplastic syndrome (MDS). When MDS is diagnosed, some patients with intestinal BD experience synchronous gastrointestinal flares. Case presentation: We report the case of a 49-year-old woman who presented with vaginal bleeding and an incidentally identified MS in the uterine cervix. Subsequent bone marrow biopsy showed simultaneous MDS without chromosomal abnormalities. This is the first reported case of concomitant MS, myelodysplastic disease, and intestinal BD. Conclusions: The accurate diagnosis of MSs that develop at non-predominant sites is crucial for a positive patient prognosis. MDS should be suspected in patients with a history of intestinal BD diagnosed with MS.